Мария Моравская в Первую мировую войну: от поэзии для детей к детскому голосу в поэзии для взрослых [Maria Moravskaya in World War I: From Poetry for Children to a Childlike Voice in Poetry for Adults] - Simonova, Olga A. (A.M.Gorky Institute of World Literature of the Russian Academy of Sciences, 2026)
This article provides the first detailed analysis of Maria Moravskaya’s (1889–1947) poetry related to war. Primarily known as a children’s poet, Moravskaya began writing for adults with the outbreak of the World War I.
The sincere and spontaneous style of her poems, as well as her use of “non-childlike” motifs such as resentment, loneliness, and longing, characterize both her poetry for children and her poetry for adults. The joyful worldview typical of her children’s verse also becomes a feature of her adult poetic works. The war heightened the autobiographical potential of Moravskaya’s writing: her turn to the theme of Poland can be explained by her Polish origins. The war theme is expressed explicitly through the motifs of homeland, childhood, and orphanhood, and implicitly reflected in the image of Cinderella. The use of the Cinderella mask as a metaphor for a maturing girl drew criticism from reviewers who perceived the poet’s lyrical voice as infantile. The experience of war prompted a shift in Moravskaya’s poetics from Symbolist to Acmeist, and the woman writer in her critical essay marked the emergence of a new poetic trend — emotionally charged poetry, characterized by everyday lyricism and war lyricism. This paper traces the evolution of Moravskaya’s
poetry from 1914 to 1915, revealing the common features of her children’s and adult texts, similar lyrical personae, and a common system of themes and motifs. For the first time, material from reviews of Moravskaya’s work from women’s magazines, previously overlooked by scholars, is included.
Неслучайный дар: К юбилею Марии Викторовны Михайловой [Not Vain Gift: On the Anniversary of Maria Viktorovna Mikhailova]